Understanding homeland security: foundations of security policy - Zaffar, Ehsan (Routledge, 2020)
Homeland security before 9/11 -- The formation of the homeland security enterprise after 9/11 -- Immigration -- Border threats, border security & risk assessment -- Intelligence -- Transportation -- Emergency management & hazards -- Cybersecurity -- Infrastructure protection & technology -- Civil rights, civil liberties & privacy.